UPAYA PENINGKATAN HASIL BELAJAR DALAM PENGENALAN PAKAIAN ADAT MELAYU MELALUI MODEL PEMBELAJARAN TAKE AND GIVE - Dirneti; Hilda Oktriyeni; Fauziah; Retno Triswandari (Universitas Karimun Prodi S1 Pendidikan Luar Biasa, 2022)
This research is classroom action research. The research subjects were fifth grade students at SDN 006 Belat District. District Splint. Karimun with the number of students as many as 22 people. The research procedure consists of 4 stages in each cycle, namely planning, implementing actions, observing and reflecting. The learning process for regional culture is carried out using the Take And Give learning model. Data was collected using the following methods: field notes, observation sheets, and learning outcomes tests. It can be concluded that students' science learning outcomes using visual media have increased, especially in the subject matter of Malay traditional clothing. In the pre-cycle, the average score was 54.5 with a learning completeness of 31.8%. In the first cycle, the average value was 51.3 with 40.9% learning completeness and in the second cycle it increased to 80.6 with 81.8% completeness. So it can be concluded that there is an increase in the average value from pre-cycle to cycle I then to cycle II and there is no need to do the third cycle.